First Record of the Ceratioid Anglerfish Species Gigantactis microdontis (Teleostei: Lophiiformes: Gigantactinidae) in the Western Pacific Ocean - Prokofiev, Artem M.; Pietsch, Theodore W. (Zootaxa, 2019)
The rare ceratioid anglerfish Gigantactis microdontis was formerly known from 12 specimens collected in the Eastern Pacific from 158° W eastward: off Hawaiian Islands, Oregon, California and Peru. Thirteenth specimen reported herein extends the known distribution of this species some 7630 km westward into the western tropical Pacific (off Caroline Islands). The newly reported specimen shows no principal differences in morphology from the previously known individuals.